Usulan Perancangan Alat Bantu Untuk Meminimalisir Kelelahan Fisik dan Mental Pekerja - Ferida Yuamita; Retno Arum Sary (Jurnal Ilmiah Teknik Industri, 2016)
CV Poetra Mandiri Karton is a company that has not been able to meet production target each day.  Based on preliminary analysis, production underproduction was due to workers’ fatigue caused by manual material handling activities in the entire production process.  To solve these problems, nordic body map (NBM) approach was applied.  Prior to work, workers experienced musculoskeletal fatigue at down waist, and they experienced musculoskeletal fatigue at up waist, left forearm, right forearm, left hand, right hand, left ankle, and right ankle after work. Based on questionnaire of National Aeronautics and Space Administration Task Load Index (NASA-TLX), average of mental workload from all three groups is quite heavy.  By using rapid entire body assessment (REBA), it is found that average value of the risk in group 1 and group 2 requires immediate action, whereas action is required by the third group.  This article also presents a trolley design that will be used in manual material handling activities.